2018
DOI: 10.1186/s13071-018-3030-2
|View full text |Cite
|
Sign up to set email alerts
|

Uranotaenia unguiculata Edwards, 1913 are attracted to sound, feed on amphibians, and are infected with multiple viruses

Abstract: BackgroundUranotaenia unguiculata Edwards, 1913 is a species of mosquito (Diptera: Culicidae) native to central Europe. Recently a novel lineage of the West Nile virus (WNV-lineage 4c) was identified in pools of adult female Ur. unguiculata. To increase the body of knowledge about this species, various trapping methods were evaluated to determine the most efficient method for capturing adult female Ur. unguiculata.ResultsSound traps collected equivalent numbers of female Ur. unguiculata as low-hanging light-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Generally, little is known about these taxa as they are rarely collected (Zittra and Waringer 2015; Zittra et al 2016 , 2017b ). Sophisticated trapping devices might be necessary to capture and investigate such rarely collected, yet not necessarily rare species (Camp et al 2018 ). The species-rich genera Aedes and Ochlerotatus mainly hibernate in their immature stages (Becker et al 2010 ) and were therefore, as expected, not recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, little is known about these taxa as they are rarely collected (Zittra and Waringer 2015; Zittra et al 2016 , 2017b ). Sophisticated trapping devices might be necessary to capture and investigate such rarely collected, yet not necessarily rare species (Camp et al 2018 ). The species-rich genera Aedes and Ochlerotatus mainly hibernate in their immature stages (Becker et al 2010 ) and were therefore, as expected, not recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…uniformis feed on frogs through the year in an opportunistic manner. Similarly, some studies have shown that Uranotaenia mosquitoes feed on anuran blood (Borkent & Belton, 2006;Toma et al, 2014;Camp et al, 2018;Reeves et al, 2018), but the feeding behaviour of species in this genus had not been documented for the species studied here. Uranotaenia rutherfordi had previously been reported only once in Sri Lanka during a mosquito survey performed in the early 1900s from the same locality, Peradeniya in Kandy District (Barraud, 1934).…”
Section: Discussionmentioning
confidence: 66%
“…lowii Borkent & Belton, 2006), Europe (Ur. unguiculata Camp et al, 2018), and Japan (Ur. nivipleurma, Ur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations